Aplicación de normas del sistema nacional de bienes estatales en área de control patrimonial - Municipalidad Distrital de Laredo, año 2018 - Caipo Zapata, Carmen Milagros Santos (2019)
The purpose of this research work is to demonstrate the Application of Standards of the National System of State Property in the Area of Property Control - District Municipality of Laredo, Year 2018 and in the same way to help the other municipalities of the region to be able to adapt to an adequate information system, for efficient control and use of its allocated resources, in this way to be able to provide a good quality of life to its citizens. For the development of this research was taken as a sample of the information obtained from the National System of State Assets – SNBE and the Office of Property Control of the District Municipality of Laredo, conducting an analysis on the internal control processes using the Analytical and Descriptive method, techniques such as data collection and analysis, as well as interviews, it was possible to determine that there was no adequate implementation of a Wealth Control System in the different offices of the Municipality. With the development of the research it is concluded that, it is sought to recommend to the authorities in charge of the Municipalities, the application of the General Law of the National System of State Goods - SNBE, has a positive effect, having the opportunity of better control Internal and the evaluation of the different activities, which allows the efficient management of the resources available to the Entity and thus avoid the improper use of the money that causes administrative mismanagement.